2018
DOI: 10.1007/s10661-018-7181-6
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil pollution with petroleum-derived substances on Porcellio scaber Latr. (Crustacea, Isopoda)

Abstract: Presented research aimed at investigating the effect of short-term contact with petroleum-derived substances (PDSs) on life parameters of Porcellio scaber Latr. (Isopoda) and accumulation of polycyclic aromatic hydrocarbons (PAHs) in its body. The influence of presence of P. scaber on the total petroleum hydrocarbons (TPH) content in soil was also determined. The following objects were established: control—unpolluted soil; soil polluted with petrol; soil polluted with diesel fuel and soil polluted with used en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…The second lot is composed by Parasitiformes, Hemiptera, Araneae and Coleoptera orders, which showed a preference for the less polluted and unpolluted zones. Rusin and Gospodarek (2016) observed in their study that petroleum-based substances in most cases did not have a negative effect on the number of spiders; on the other hand, Gospodarek et al (2019)survival and body mass change of P. scaber reared in investigated soils were observed. The delivered food was not contaminated with PDSs.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The second lot is composed by Parasitiformes, Hemiptera, Araneae and Coleoptera orders, which showed a preference for the less polluted and unpolluted zones. Rusin and Gospodarek (2016) observed in their study that petroleum-based substances in most cases did not have a negative effect on the number of spiders; on the other hand, Gospodarek et al (2019)survival and body mass change of P. scaber reared in investigated soils were observed. The delivered food was not contaminated with PDSs.…”
Section: Resultsmentioning
confidence: 86%
“…Hymenoptera abundances did not show a clear tendency; we observed the lowest abundances in zones 1 and the highest in zones 2. It was observed that Isopoda and Hymenoptera can take advantage of high levels of contamination (Faulkner and Lochmiller, 2000), and according to Gospodarek et al (2019)survival and body mass change of P. scaber reared in investigated soils were observed. The delivered food was not contaminated with PDSs.…”
Section: Resultsmentioning
confidence: 91%
“…Samiullah (1985) suggested that organisms that inhabit shallow water environments, and intertidal zones, in addition to those that have to cross the air–water interface are most affected. The uptake of PH by marine organisms has been the subject of many field and laboratory studies covering marine mammals (Fair et al ., 2010; Moon et al ., 2011), seabirds (Lance et al ., 2001; Romero et al ., 2018), reptiles (Ylitalo et al ., 2017; Frasier et al ., 2020), fishes (Afifi et al ., 2017; Beg et al ., 2018) and crustaceans (Knap et al ., 2017; Gospodarek et al ., 2019). Exposure to waters mixed with crude oil can result in many adverse effects on marine biota as oil components such as naphthalenes can be taken up into organisms’ tissues (Varanasi & Malin, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Soil pollution with petroleum-derived substances (PDSs) entails a strong negative effect on both its physicochemical properties [1,2] and biological activity [3][4][5][6][7], as well as causing far-reaching changes in organisms indirectly exposed to these pollutants (e.g., herbivores) [8][9][10]. The components that are especially dangerous to the environment are polycyclic aromatic hydrocarbons (PAHs) [11]. Efficient methods for their safe neutralization are still being sought through bioaugmentation or adding surfactants [12,13], optimization of fertilization [14], rhizoremediation [15] or electrobioremediation [16].…”
Section: Introductionmentioning
confidence: 99%